Backpropagation and Radial Basis Function Methods for Predicting Rainfall in Sukabumi City Using Artificial Neural Networks: A Comparative Analysis - Sholahudin Sholahudin; Andika Kurniawan; Wahyu Dwi Nurhidayat; Muhammad Alif Alfaturisya; Ilyas Aminuddin; Anggi Dwiyanto; Yordanius Damey; Akhmad Afifuddin; Muhammad Syahrul Fauzi; Fandi Sugih; Muchtar Ali Setyo Yudono (FIDELITY : Jurnal Teknik Elektro, 2022)
The weather has a substantial impact on the ability to live organisms to carry out everyday activities, particularly outside activities. Weather data is helpful in various fields, including marine, aviation, and agriculture. The maritime domain is beneficial for establishing the optimal navigation time for a fisherman, the aviation domain helps reduce climate-related mishaps, and the agriculture sector uses weather information to develop harvest season models for agricultural products. Indonesia is a tropical nation with heavy precipitation. Utilized for various objectives, rainfall forecasting models seek the utmost precision, particularly in specialized areas such as flood control. This study is based on two techniques: the Radial Basis Function Neural Network (RBFNN) and Backpropagation Neural Network (BPNN) techniques using multiple training functions. The RBFNN approach yields less accurate results for predicting precipitation, but the multi-practice BPNN method yields more accurate results.